2021
DOI: 10.1088/1741-2552/abda0a
|View full text |Cite
|
Sign up to set email alerts
|

The microglia response to electrical overstimulation of the retina imaged under a transparent stimulus electrode

Abstract: Objective. We investigated using the morphological response of retinal microglia as indicators of tissue damage from electrical overstimulation by imaging them through an optically transparent stimulus electrode. Approach. To track the microglia, we used a transgenic mouse where the microglia expressed a water soluble green fluorescent protein. The clear stimulus electrode was placed epiretinally on the inner limiting membrane and the microglia layers were imaged using time-lapse confocal microscopy. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(81 reference statements)
2
0
0
Order By: Relevance
“…Real-time imaging studies of transgenic mice microglia labeled with green fluorescent protein (GFP) showed focused laser injury in CNS and retinal tissue caused their processes to become oriented centripetally and extended into small local lesions (Davalos et al, 2005;Nimmerjahn et al, 2005;Eter et al, 2008;Lee et al, 2008). Although we were unable to label microglia stably using lectins in the rabbit retina a priori for reliable real-time tracking post stimulation, the local orienting movements of these microglia cell processes around the stimulated zone in the rabbit retina is very similar to our previous results using real-time imaging in the CX3CR1 GFP transgenic mouse retina using a smaller transparent stimulation tube electrode and the same high charge density stimulation (Yohannes et al, 2021). Here we also found, imaging up to 90 min.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Real-time imaging studies of transgenic mice microglia labeled with green fluorescent protein (GFP) showed focused laser injury in CNS and retinal tissue caused their processes to become oriented centripetally and extended into small local lesions (Davalos et al, 2005;Nimmerjahn et al, 2005;Eter et al, 2008;Lee et al, 2008). Although we were unable to label microglia stably using lectins in the rabbit retina a priori for reliable real-time tracking post stimulation, the local orienting movements of these microglia cell processes around the stimulated zone in the rabbit retina is very similar to our previous results using real-time imaging in the CX3CR1 GFP transgenic mouse retina using a smaller transparent stimulation tube electrode and the same high charge density stimulation (Yohannes et al, 2021). Here we also found, imaging up to 90 min.…”
Section: Discussionsupporting
confidence: 85%
“…In primates, microglial cells are also distributed throughout the central retina (except in the foveola) but at lower densities than Müller cells, like their distribution in the rabbit ( Ashwell, 1989 ; Singaravelu et al, 2017 ). This cellular distribution presumably would result in local injury responses to overstimulation similar to those described here and in Yohannes et al (2021) . In contrast, the fine processes of inner retinal astrocytes are largely absent from the avascular rabbit retinal model, but are present at low densities in the nerve fiber and ganglion cell layer of the vascular retinas of primates and humans ( Schnitzer and Karschin, 1986 ; Ramirez et al, 1994 ).…”
Section: Discussionsupporting
confidence: 59%